1994
DOI: 10.1200/jco.1994.12.4.769
|View full text |Cite
|
Sign up to set email alerts
|

Randomized comparison of MACOP-B with CHOP in patients with intermediate-grade non-Hodgkin's lymphoma. The Australian and New Zealand Lymphoma Group.

Abstract: CHOP chemotherapy produced results equivalent to those of MACOP-B in patients with intermediate-grade NHL and with significantly fewer toxic complications. Despite relatively poor results in some patient subgroups, CHOP remains the standard chemotherapy for this disease, against which all new regimens should be compared.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0
3

Year Published

1998
1998
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(31 citation statements)
references
References 21 publications
2
26
0
3
Order By: Relevance
“…Before the advent of rituximab, a number of dose-intensified cytotoxic therapies were introduced but these regimens failed to provide substantial improvement over the standard anthracycline based combination of cyclophosphamide, vincristine, doxorubicin and prednisone (CHOP) or CHOP-like chemotherapy. [6][7][8][9][10] In contrast, the addition of rituximab, a monoclonal antibody with a different mechanism of action than traditional cytotoxic chemotherapy, significantly improved the results of initial therapies. [1][2][3][4] Based on these and other studies, R-CHOP (rituximab-cyclophosphamide, doxorubicin, vincristine, and prednisone) has become the standard of care therapy for patients with newly diagnosed aggressive B-cell lymphoma.…”
Section: Introductionmentioning
confidence: 99%
“…Before the advent of rituximab, a number of dose-intensified cytotoxic therapies were introduced but these regimens failed to provide substantial improvement over the standard anthracycline based combination of cyclophosphamide, vincristine, doxorubicin and prednisone (CHOP) or CHOP-like chemotherapy. [6][7][8][9][10] In contrast, the addition of rituximab, a monoclonal antibody with a different mechanism of action than traditional cytotoxic chemotherapy, significantly improved the results of initial therapies. [1][2][3][4] Based on these and other studies, R-CHOP (rituximab-cyclophosphamide, doxorubicin, vincristine, and prednisone) has become the standard of care therapy for patients with newly diagnosed aggressive B-cell lymphoma.…”
Section: Introductionmentioning
confidence: 99%
“…Retrospective reviews in the 1990s suggested an association between an increase in relative dose intensity (RDI) and improved response rates and survival [2,3]. This association was consistent with in vitro studies demonstrating a log-linear relationship between chemotherapy dose and tumour cell kill [4][5][6][7].…”
Section: Introductionmentioning
confidence: 55%
“…Despite the publication of trials comparing different chemotherapy regimens, at the time of trial design there were no studies specifically evaluating dose as the only treatment variable in aggressive NHL [2,3]. In this context, the Australian and New Zealand Lymphoma Group (now the ALLG) designed a study to compare the effectiveness of a high-dose (intensive) CEOP (cyclophosphamide, epirubicin, vincristine, and prednisolone) regimen (i-CEOP) with a standard CEOP regimen (s-CEOP) in patients with advanced aggressive NHL with epirubicin and cyclophosphamide doses in i-CEOP double those in s-CEOP.…”
Section: Introductionmentioning
confidence: 99%
“…Although preliminary studies invariably showed very high response rates for the so-called second-and third-generation regimens, a definitive demonstration of superiority over the firstgeneration combinations, in particular the CHOP regimen (cyclophosphamide, doxorubicin, vincristine and prednisone), has not been reached (Fisher et al, 1993;Cooper et al, 1994).…”
Section: Discussionmentioning
confidence: 99%